Performance Analysis Of Consumer Forum Redressal System Of India - Kaur, Kamalpreet (Gyan Management Journal, 2021)
The government has enacted various social legislations from time to time to protect the rights and interest of the consumers. Among these, The Consumer Protection Act, 1986 is the most progressive and under this act various tribunals were set up at district level and state level with National Consumer Disputes Redressal Commission (NCDRC) as an apex. There is need to study that how many consumers with complaints approach these tribunals and how they are being entertained. In the present paper an effort is made to analyze the performance of State Consumer Redressal Commission of Chandigarh for the time period of 2011 to 2018. The study showed that the disposal rate of Chandigarh redressal agencies is higher than total disposal rate in India since inception. Further, the study concluded that redressal agencies of Chandigarh indicated significance difference in the means of cases filed, disposed and pending. It can be suggested that accelerating the disposal rate will stretch better results.